Elites, nonelites, and power : the critical legacy of elite theory from Marx to Lachmann, and then beyond - Emigh, Rebecca Jean; Riley, Dylan (Political power and social theory ;, 2024)
In a world of vertiginous inequality, escalating ecological disaster, and extraordinary political and economic turbulence generated by a winner-take-all society seemingly designed to concentrate privilege and power in the hands of a very few, the central question that faces social science--and indeed the world--is whether social protest will change anything, or whether elites will continue to lead the planet and its population to disaster. All important topics of contemporary social science, including racial justice, environmental change, immigration, economic inequality, and education, to name a few, revolve around this issue. Elites, Nonelites, and Power explores how the question of the power of elites, and the conditions under which that power might be tamed, lie at the heart of social science today. Bringing together a cutting-edge set of multidisciplinary papers on power, elites, and nonelites, that weigh in on these central issues of the world and social science, the collection consider these topics in a new, inclusive way, by drawing in researchers who deal with topics central to elite theory, but who might not be represented in more classic statements of it. A "go to" piece for several generations of scholars, this is a compelling volume for scholars across the social sciences interested in elite theory.